Glucagon-Like Peptide-1, Diabetes, and Cognitive Decline: Possible Pathophysiological Links and Therapeutic Opportunities. (17th May 2011) - Mossello, Enrico; Ballini, Elena; Boncinelli, Marta; Monami, Matteo; Lonetto, Giuseppe; Mello, Anna Maria; Tarantini, Francesca; Baldasseroni, Samuele; Mannucci, Edoardo; Marchionni, Niccolò
Abstract : Metabolic and neurodegenerative disorders have a growing prevalence in Western countries. Available epidemiologic and neurobiological evidences support the existence of a pathophysiological link between these conditions. Glucagon-like peptide 1 (GLP-1), whose activity is reduced in insulin resistance, has been implicated in central nervous system function, including cognition, synaptic plasticity, and neurogenesis. We review the experimental researches suggesting that GLP-1 dysfunction might be a mediating factor between Type 2 diabetes mellitus (T2DM) and neurodegeneration. Drug treatments enhancing GLP-1 activity hold out hope for treatment and prevention of Alzheimer's disease (AD) and cognitive decline.